Prognostic Impact of the Tumor Marker CA 15-3 in Patients With Breast Cancer and Bone Metastases Treated With Palliative Radiotherapy - Nieder, Carsten (J Clin Med Res, 2017)
BACKGROUND: The aim of the study was to explore the prognostic impact of different abnormal blood tests and the tumor marker CA 15-3 as well as established parameters such as disease extent and receptor status in patients with bone metastases from breast cancer who received palliative radiotherapy in addition to contemporary systemic treatment. METHODS: This was a retrospective uni- and multivariate analysis of 118 female patients treated in the time period from 2007 to 2014 (median follow-up 28 months). RESULTS: The median age was 61 years and the median time interval from the initial diagnosis of breast cancer was 57 months (median time interval from metastatic disease to radiotherapy was 7 months). Only 16% of patients had normal serum CA 15-3. HER2 receptor status correlated with CA 15-3. The median survival was 17.6 months (lowest CA 15-3 quartile), 14.7 months (intermediate), and 6.9 months (highest quartile) (P = 0.002). However, multivariate analysis showed that survival was influenced by extent of extra-skeletal metastases, pleural metastases/effusion, lung metastases, estrogen receptor status, serum C-reactive protein, and anemia with need for blood transfusion (all P < 0.05) rather than CA 15-3. CONCLUSIONS: Survival was highly variable. The tumor marker CA 15-3 did not provide independent prognostic information. Nevertheless, the results of simple blood tests contributed to the multivariate prognostic model.